An improved ultra-low-phase noise tunable YIG oscillator operating in the 6–12 GHz range - Stein, Wadim; Huber, Florian; Bildik, Saygin; Aigle, Michael; Vossiek, Martin (47th European Microwave Conference (EuMC), 2017)
This paper presents the improvement of a conventionally designed state-of-the-art yttrium-iron-garnet tuned oscillator with the main focus on the minimization of the phase noise. The employment of modern CAD tools allows for accurate oscillator optimization resulting in a phase noise performance below -133 dBc/Hz at a frequency offset of 100 kHz over the entire range of 6-12 GHz. The presented oscillator is modeled as a one-port oscillator employing a SiGe hetero bipolar transistor as a reflection amplifier and a loop-coupled YIG sphere resonator, modeled and simulated in a commercial FEM 3D-fullwave simulator considering all coupling effects and respective parasitics. The achieved phase noise is compared to a number of state of the art YIG oscillators around the frequency offset of 10 kHz, 100 kHz and 1 MHz. Finally some further phase noise improvements over the frequency range of 6-12 GHz are show
lhft_intern.bib::Stein2017